High Performance and Cycling Stability Supercapacitors Employing MnS@Polypyrrole Nanocomposites as Cathode Material - Gülen, Mahir; Gülen, Mahir (My University, 2023)
In this study, MnS metal sulphide was incorporated into polypyrrole (PPy) matrix, and the fabricated nanocomposites were used for the first time as active electrode in supercapacitor (SC) architecture. MnS was obtained in a short time (15 min) via simple microwave technique, and the nanocomposite was synthesised successfully with electropolymerization of PPy in presence of MnS on nickel foam. Incorporation of MnS changed the growth mechanism of PPy, leading to increase in surface area, electrocatalytic activity and conductivity of the resulted nanocomposites. More importantly, MnS@PPy electrode exhibited a specific capacitance (Cs) of 1102 F/g which is approximately 5.6 times higher than that of the bare PPy (197 F/g). Furthermore, energy density (Ed) of the bare PPy was determined as 4.37 W/kg, by incorporation of MnS into PPy matrix the Ed value increased to 24.5 W/kg. On the other hand, after 1000 charge/discharge cycles, the cycle stability of the bare PPy remained at 72%, while MnS@PPy nanocomposite electrode is 95 %. The reasons for these improvements can be listed as; i) the increase in conductivity of nanocomposite stem from the synergistic effect between MnS and PPy, ii) the enlargement of the active surface area, iii) the increase in the ion diffusion rate, iv) the improvement of charge transfer kinetics and v) the increase in stability against volume change. In the light of the results obtained from this study, it can be said that the MnS@PPy structured nanocomposite is a promising candidate for commercialization of SC applications.
Keywords: Mühendislik; Elektrik ve Elektronik; Nanobilim ve Nanoteknoloji; Renewable energy; Supercapacitor; Energy storage; Nanocomposites